Propuesta de desarrollo turístico para el sistema lacustre del parque nacional Yacuri de la parroquia Jimbura, cantón Espíndola - Jiménez Alverca, Rocío del Carmen (2022)
The present investigative work "Tourism Development Proposal for the Yacuri National Park Lacustrine System of the Jimbura parish, Espíndola canton" was proposed based on the need to contribute to the tourist strengthening of the park and its zone of influence. For this, a general objective was proposed: Design a Proposal for the Tourist Development of the Lake System "Lagunas de Jimbura" of the PNYC of the Jimbura parish, Espíndola canton, in addition, three specific objectives were established, the same ones that allowed to solve the problem found. For the analysis of the current tourist situation of the Lacustrine System a first objective was raised, on-site visits, surveys and interviews were carried out, likewise, the methodologies were used; Manual of Local Diagnosis of Carla Ricaurte and the Summary Sheets of MINTUR Tourist Attractions, which allowed to identify the state of the tourist attractions and to evaluate the current tourist situation of the Jimbura parish. To determine the capacity of use of the tourist resources proposed in the second objective, the information obtained in the tourist diagnosis, the Range of Opportunities for Visitors in Protected Areas (ROVAP) methodology and the Tourist Load Capacity were used as a basis on Cifuentes, thus determining the opportunities offered by the Yacuri National Park in the area of public use and tourism and the Load Capacity of each of the attractions studied, likewise, the existing strengths and weaknesses were evaluated and strategies were proposed. Strengthening necessary to work on tourism development through the SWOT Matrix and Strategic SWOT. In the third objective to define the scope of the tourism development proposal, the Logical Framework Methodology was used, work was carried out on the tourism improvement strategies determined in the second objective, for this, the weak tourism management of the park was determined as a central problem. , then the necessary means and ends were identified so that the development proposals for the Jimbura Lagoons are fulfilled. Among the results obtained, it was highlighted that there is minimal use of the tourist resources of the place, poor infrastructure, minimal promotion and dissemination of attractions and lack of management by the authorities. Finally, it is recommended that the authorities carry out comprehensive work for the benefit of tourism activity and execute tourism development projects that link the local community and promote development.